2021
DOI: 10.2147/dmso.s310751
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Accumulation Product is Associated with Urinary Albumin-creatinine Ratio in Chinese Prediabitic Population: A Report from the REACTION Study

Abstract: Background Lipid accumulation product (LAP) as a powerful marker of visceral obesity is an independent risk factor of chronic kidney disease. The present study attempted to explore the association between LAP and albuminuria in prediabetic individuals. Methods We conducted a cross-sectional study and enrolled 26,529 participants with prediabetes over 40 years old with prediabetes from seven provinces in China. LAP was calculated from waist circumference and fasting trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
2
2
0
1
Order By: Relevance
“…Additionally, the correlation of LAP quartiles with CKD prevalence in female subjects was attenuated but retained significance after further adjusting for blood pressure, LDL-C, prevalence of T2DM, and hypoglycaemic drugs in Model 4, suggesting that diabetes, hypertension, and dyslipidaemia added to the risk of CKD prevalence and probably weakened the correlation of LAP with of risk of CKD prevalence. Further stratified analysis showed that a significant correlation of higher LAP quartiles with an increased risk for CKD prevalence was only detected in hypertensive subjects but not in those with normal blood pressure, which was generally in line with several previous studies [ 28 , 30 , 31 ], suggesting that hypertension might be associated with the prevalence of CKD. More importantly, an interaction of hypertension with LAP on CKD prevalence was also observed, indicating that hypertension and elevated LAP may synergistically increase the risk of CKD prevalence, and hypertension might a stronger factor affecting the relationship between LAP and CKD prevalence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, the correlation of LAP quartiles with CKD prevalence in female subjects was attenuated but retained significance after further adjusting for blood pressure, LDL-C, prevalence of T2DM, and hypoglycaemic drugs in Model 4, suggesting that diabetes, hypertension, and dyslipidaemia added to the risk of CKD prevalence and probably weakened the correlation of LAP with of risk of CKD prevalence. Further stratified analysis showed that a significant correlation of higher LAP quartiles with an increased risk for CKD prevalence was only detected in hypertensive subjects but not in those with normal blood pressure, which was generally in line with several previous studies [ 28 , 30 , 31 ], suggesting that hypertension might be associated with the prevalence of CKD. More importantly, an interaction of hypertension with LAP on CKD prevalence was also observed, indicating that hypertension and elevated LAP may synergistically increase the risk of CKD prevalence, and hypertension might a stronger factor affecting the relationship between LAP and CKD prevalence.…”
Section: Discussionsupporting
confidence: 91%
“…The present study also showed that female subjects with CKD had significantly higher BMI and prevalence of obesity compared with those without CKD, and BMI was positively correlated with CKD prevalence. Further stratified analysis by BMI revealed that a significant correlation between higher LAP quartiles and risk of CKD prevalence was only detected in overweight subjects, which was similar to a previous study [ 28 ], suggesting that being overweight may correlate with the prevalence of CKD via several modifiable atherosclerotic and cardiometabolic risks, as well as endothelial dysfunction. Moreover, after adjusting for sex, age, and BMI, the correlation of LAP quartiles with risk of CKD prevalence in female subjects was attenuated, indicating that female sex, older age, and overweight status added to the risk of CKD prevalence and altogether probably weakened the correlation of LAP quartiles with risk of CKD prevalence.…”
Section: Discussionsupporting
confidence: 87%
“…CVAI is a novel surrogate for the assessment of metabolic health and the prediction of T2DM. BAI is a marker of adipose function and distribution, and LAP is associated with insulin resistance, reflecting central fat accumulation ( 29 , 30 ). Additionally, mounting evidence supports that these visceral obesity-related indices better identify individuals at elevated risk for metabolic diseases such as T2DM and CVD ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of previous cross-sectional studies. [39][40][41] Kidney damage may be more sensitive to metabolic disorder. However, more cohort studies are needed to confirm this finding.…”
Section: Discussionmentioning
confidence: 99%